Production of Scale Drop Disease Virus Self-assembled Major Capsid Protein Nanoparticles for Fish Vaccine Development - Chansuwan, Surawat; Akeprathumchai, Saengchai; Poomputsa, Kanokwan; Rattanarojpong, Triwit; Mekvichitsaeng, Phenjun (Thai Journal of Science and Technology, 2021)
Scale drop disease virus (SDDV) causes scale drop syndrome in Asian sea bass. Vaccination is considered an effective method for the control of this disease. SDDV vaccines that have been tested are inactivated vaccine and subunit vaccine. The chemical or physical treatment used to inactivate the virus and denaturing agent used for subunit vaccine purification have been known to modify their antigenicity. This usually results in a short immune response, weaker cell-mediated and mucosal immune responses, and possibly less effective in preventing viral entry. Therefore, new form of an antigen called self-assembled protein nanoparticles (SAPNs) to improve antigen stability and immunogenicity was proposed. These SAPNs were obtained from the oligomerization of recombinant SDDV major capsid proteins (MCP) produced by the baculovirus expression vector system. A genetically engineered baculovirus vector was constructed and used for expression of His-tag fused SDDV MCP gene in insect cells as confirmed by reverse transcription PCR (RT-PCR). A specific protein band at approximately 53 kDa, corresponding to the recombinant His-tag MCP protein, was detected in the baculovirus-infected insect cells by Western blot analysis. This recombinant MCP protein was partially purified by ultracentrifugation using double layers of 25 and 70 % sucrose. The electron micrograph of the purified sample revealed many particles with sizes ranging from 50-100 nm. These recombinant MCP proteins seem to be able to self-assemble to form nanoparticles in well-ordered arrays that mimic the repetitiveness, geometry, and shape of the SDDV virus. It is anticipated that a stable and better immunogenicity SDDV vaccine could be developed.